Carvacrol previne disfunção erétil de ratos em modelo de envelhecimento induzido por D-galactose - Rezende, Mathania Silva de Almeida (2020)
Erectile dysfunction (ED) is defined as the inability to achieve and/or maintain an erection sufficient for satisfactory sexual intercourse, with aging being one of the risk factors involved in its development. There is an increasing evidence suggesting that oxidative stress is a key mediator of changes in endothelial function and penile vascular tone in the aging process. Thus, reducing the levels of reactive oxygen species (ROS) can be an important process to preserve the bioactivity of the penile vasculature. Antioxidant compounds, such as carvacrol, limit the damage caused by ROS and, therefore, have benefits for the treatment of ED. The aim of the present work is to characterize a new experimental model of ED in aging induced by D-galactose, as well as to evaluate the effects of carvacrol on the erectile function of these rats. For this, the animals were separated into five groups: control treated with vehicle (CTL), D-galactose 150 mg/kg (DGAL), D-galactose 150 mg/kg+carvacrol 50 or 100 mg/kg (DGAL+CVC50 or 100) and D-galactose 150 mg/kg+sildenafil 1.5 mg/kg (DGAL+SD1.5). All animals were subjected to daily administrations, intraperitoneal (D-galactose) and oral (carvacrol and sildenafil), for eight weeks. The experimental protocols were previously approved by the Ethics Committee on the Use of Animals of the Universidade Federal da Paraíba, Nº. 9706070319. Initially, the physical appearance of the animals was analyzed and it was observed that the treatment of animals in the DGAL group showed aging characteristics, such as severe fur loss, curly and opaque fur with different shades, differently from animals in the CTL, DGAL+CVC50 or 100 and DGAL+SD1.5 groups that had a healthy aspect. The groups of animals showed a gradual increase in body weight, and had no difference in the glycemic levels. Erectile function was assessed by the intracavernosal pressure/mean arterial pressure (ICP/MAP) ratio. The ICP/MAP in the DGAL group was significantly reduced when compared to the CTL group, demonstrating the development of ED. The treatments with carvacrol or sildenafil improved this parameter, suggesting an improvement in erectile function by these treatments. Regarding the cavernous reactivity, the DGAL and DGAL+SD1.5 groups presented a hypercontractility induced by phenylephrine or electrical field stimulation, when compared with the CTL and DGAL+CVC100 groups, respectively. The treatment with carvacrol significantly reduced this hypercontractility. The relaxing response induced by acetylcholine was significantly reduced in the DGAL and DGAL+SD1.5 groups when compared with the CTL group. This effect was prevented by treatment with carvacrol. The relaxation mediated by sodium nitroprusside did not show statistical differences between the groups. In histological sections of the corpora cavernosa (CC), the DGAL group showed an increase in the production of superoxide anions, when compared to the CTL group, while treatment with carvacrol and sildenafil prevented this increase. Structural changes were observed with the treatment of the DGAL group, observing a decrease in the total area of the CC, when compared with the CTL group. The DGAL+CVC100 group was able to prevent this change, unlike the DGAL+CVC50 and DGAL+SD1.5 groups. The biomarker senescence method (senescence associated with β-galactosidase - AS-β-gal) was used and it was observed that the DGAL group induced an increase in the positive staining of ASβ-gal activity in cavernous tissue compared to the group CTL. Treatment with cavacrol and sildenafil was able to prevent this increase. In conclusion, these results demonstrate, for the first time, that the induced by D-galactose aging model promoted the development of ED, hypercontractility, endothelial dysfunction, in addition to increasing the ROS and decreasing the erectile components essential for penile erection and increased senescence in penile tissue, and the treatment with carvacrol prevented all changes and damage associated with this model.